2014
DOI: 10.1590/s0104-12902014000200017
|View full text |Cite
|
Sign up to set email alerts
|

Direitos das parturientes: conhecimento da adolescente e acompanhante

Abstract: ResumoEste estudo busca analisar o conhecimento de adolescentes e seus acompanhantes acerca dos seus direitos no parto. Trata-se de uma investigação qualitativa e exploratória, realizada a partir de um recorte da pesquisa intitulada "Atenção humanizada ao parto de adolescentes". O local de estudo foi um hospital universitário do Sul do Brasil e os sujeitos foram adolescentes que tiveram partos pelo Sistema Único de Saúde no hospital investigado e seus familiares. O critério para inclusão no estudo foi conhecer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
0
5
0
18
Order By: Relevance
“…Although this document 6 was published in 2005, its limited publicizing has stopped it from being used as an instrument for ensuring the presence of the companion 6 - 7 . …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this document 6 was published in 2005, its limited publicizing has stopped it from being used as an instrument for ensuring the presence of the companion 6 - 7 . …”
Section: Discussionmentioning
confidence: 99%
“…This legal support aims to protect women’s rights, facilitating the companion’s remaining present during obstetric inpatient treatment. However, studies have identified that ignorance and failure to comply with this Law continue to be considerable 6 - 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of knowledge of the population interferes with the matter of autonomy of the mother and her family in the labor process. Many times, information is not presented, thereby ignoring the respect for the rights of citizens [18].…”
Section: It's Great! (Amethyst) Open Journal Of Nursingmentioning
confidence: 99%
“…A atenção concedida ao indivíduo que servirá de apoiador durante todo o mecanismo de parturição dependerá da aplicação de práticas comprovadamente eficazes e estabelecimento de vínculos fundamentados em princípios éti-cos. A garantia de autonomia, privacidade e as trocas com a gestante e seu familiar são essenciais para adoção de condutas futuras (Carvalho, Kerber, 2014 (Brasil, 2005). Portanto, ao considerarmos esta legislação, não se caracteriza como atribuição de nenhum profissional fomentar a criação de parâmetros que avaliem a pertinência de uma pessoa, selecionada pela cliente, para protagonizar junto a mesma o momento do nascimento.…”
Section: Relevância Do Acompanhante Nas Consultas De Pré-natalunclassified